Ballistic quantum transport in a nanoscale metal-oxide-semiconductor field effect transistor - Arora, Vijay K.; Tan, Michael L. P.; Saad, Ismail; Ismail, Razali (American Institute of Physics, 2007)
The ballistic saturation velocity in a nanoscale metal-oxide-semiconductor field effect transistor (MOSFET) is revealed to be limited to the Fermi velocity in a degenerately induced channel appropriate for the quasi-two-dimensional nature of the inverted channel. The saturation point drain velocity is shown to rise with the increasing drain voltage approaching the intrinsic Fermi velocity, giving the equivalent of channel-length modulation. Quantum confinement effect degrades the channel mobility to the confining gate electric field as well as increases the effective thickness of the gate oxide. When the theory developed is applied to an 80 nm MOSFET, excellent agreement to the experimental data is obtained.